A Systematic Review of Naldemedine and Naloxegol for the Treatment of Opioid-Induced Constipation in Cancer Patients - Ursula K. Braun; Leanne K. Jackson; Mary A. Garcia; Syed N. Imam (MDPI AG, 2024)
Background: Opioid-induced constipation (OIC) is a pervasive and distressing side effect of chronic opioid therapy in patients with cancer pain, significantly impacting their quality of life. Peripherally acting μ-opioid receptor antagonists (PAMORAS) were developed for treatment-resistant OIC but most studies were conducted with non-cancer patients. Objective: to discuss two oral formulations of PAMORAs, naldemedine and naloxegol, and to review available evidence of the effectiveness of these drugs for OIC in cancer patients. Methods: a comprehensive search to identify primary literature for either naldemedine or naloxegol for OIC in cancer patients. Results: Only three prospective randomized, double-blind, placebo-controlled clinical trials for naldemedine enrolling cancer patients were identified; the results of a subgroup analysis of two of those studies and two non-interventional post marketing surveillance studies of these trials are also reported here. For naloxegol, only two randomized controlled trials were identified; both were unsuccessful in enrolling sufficient patients. An additional four prospective non-interventional observational studies with naloxegol were found that enrolled cancer patients. There were significantly higher rates of responders in the PAMORA groups than in the placebo groups. The most common side effect for both PAMORAs was diarrhea. Limitations: All studies were industry-funded, and given that only three trials were randomized controlled studies, the overall quality of the studies was lacking. Conclusion: Naldemedine or naloxegol appeared safe and useful in the treatment of OIC in cancer patients and may improve their quality of life. Larger-scale randomized placebo-controlled studies of PAMORAs in cancer patients would strengthen existing evidence.